Vegetarianism in the anarchist press of the Río de la Plata (Quinto Sol, 2022)
This article tracks and analyzes the presence of vegetarianism in the Río de la Plata anarchist press throughout the first three decades of the 20th century. Through the review of periodical sources and other printed documents published in Buenos Aires and Montevideo between 1900 and 1930, the hypothesis maintained is that, in the anarchist newspapers, vegetarianism was understood from two heterogeneous perspectives, from which emerged two different diffusion strategies. On the one hand, it was promoted as an antimilitarist ethic, which understood that abstaining from meat consumption implied a habit of conduct on which rested the hope of a world without armed conflicts. Later, it was also promoted as part of a naturopathic diet, according to which the maintenance of a vegetarian diet was a physiological prescription essential for achieving a healthy life. Finally, based on the recovery of different debates raised within the anarchist press due to the presence in it of vegetarian propaganda, it investigates the discomfort that the latter generated and the difficulties it had to overcome to find a place in the anarchist militancy.
Keywords: anarchism; vegetarianism; antimilitarism; naturism